The performance of irrigation associations in Turkey after the transfer - Cakmak E.H.; Erdogan F.C.; Cetik M. (Irrigation systems performance, 2005)
Regional and cropping pattern diversities are the basic criteria used in selecting four irrigation associations in Turkey to trace the path of their post-transfer performance in operation and maintenance (O&M) activities. Results suggest that irrigation associations are able to fulfill irrigation tasks to a large extent with enhanced equipments. Fee collection rates are at improved levels despite delays in payments, mainly due to the mismatch of the financial and production calendars. Cotton dominant cropping patterns lead higher and increasing O&M expenditures compared to cereals. Although the transfers increased the adjustment ability of farmers to exogenous factors, the findings suggest that it is still too early to decide on the sustainability of the transfer program.
2. WASAMED Workshop: Irrigation Systems Performance, 2004/06/24-28, Hammamet (Tunisia)